PENGABDIAN MASYARAKAT PERJANJIAN JUAL BELI - Fikri Aliansyah; Hermawan; Budiman (PT. Adriani Mandiri Publisher, 2026)
A sale and purchase agreement is one of the forms of agreement commonly carried out in everyday life. However, in practice, some members of the community still conduct buying and selling transactions verbally or without written documentation, which may lead to misunderstandings and disputes in the future. This community service activity aimed to improve the understanding and legal awareness of youth in Banyurip Village, Sambungmacan District, Sragen Regency, regarding the importance of written sale and purchase agreements as a form of legal protection and an effort to prevent default. The activity employed an educational and participatory approach consisting of observation, socialization, training, assistance, monitoring, and evaluation. The materials provided covered the definition, forms, and types of sale and purchase agreements, the importance of written agreements, and the practical procedures for preparing and completing written agreements, including the use of stamp duty and agreements without stamp duty. The results of the activity indicated that the socialization, training, and assistance improved the participants' understanding of the importance of written documents in sale and purchase transactions. The participants also gained practical knowledge regarding the preparation and implementation of sale and purchase agreements, enabling them to clarify the rights and obligations of the parties and minimize potential conflicts and disputes. This activity is expected to increase community awareness of the importance of using written agreements in sale and purchase transactions as a form of legal protection.